2019
DOI: 10.1037/emo0000411
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subjective well-being following the U.S. Presidential election of 2016.

Abstract: This investigation examined predictors of changes over time in subjective well-being (SWB) after the 2016 United States presidential election. Two indicators of SWB—general happiness and life satisfaction—were assessed three weeks before the election, the week of the election, three weeks later, and six months later. Partisanship predicted both indicators of SWB, with Trump supporters experiencing improved SWB after the election, Clinton supporters experiencing worsened SWB after the election, and those who vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…It stands to reason that a vote for or against President Trump would have differential impact on voter wellbeing. In one longitudinal study that measured individuals before and after the 2016 U.S. presidential election, Lench et al (2018) observed that Trump supporters experienced an increase in subjective wellbeing, whereas individuals who supported Clinton or neither candidate reported a decline in wellbeing for up to 6 months after the election. Conceivably, the links between spiritual appraisals and post-election adjustment could be moderated by whether the individual voted for the winning versus losing candidate.…”
Section: Voting To Win Voting To Losementioning
confidence: 99%
“…It stands to reason that a vote for or against President Trump would have differential impact on voter wellbeing. In one longitudinal study that measured individuals before and after the 2016 U.S. presidential election, Lench et al (2018) observed that Trump supporters experienced an increase in subjective wellbeing, whereas individuals who supported Clinton or neither candidate reported a decline in wellbeing for up to 6 months after the election. Conceivably, the links between spiritual appraisals and post-election adjustment could be moderated by whether the individual voted for the winning versus losing candidate.…”
Section: Voting To Win Voting To Losementioning
confidence: 99%
“…This same survey also found that nearly 60% of Americans felt stressed by the current climate of sociopolitical polarization (American Psychological Association, 2017). Psychological effects were also documented in a study by Lench et al (2018) examining post-election subjective wellbeing (SWB). Not only did they discover a significant change in people's perceptions of their quality of life after the election, but they also found that partisanship predicted these changes such that SWB improved among Trump supporters and decreased for Clinton supporters.…”
Section: Introductionmentioning
confidence: 99%
“…The study's limitations include convenience sampling, a nonrepresentative sample, and an inability to identify how non‐MTurk participants accessed the survey. Aside from one disability organization, recruitment targeted a general population, resulting in n = 855 respondents from MTurk, a crowd‐sourced recruitment strategy previously used to assess the 2016 election's impact (Cepeda et al, 2018; Lench et al, 2019). We note recent U.S. data finding that one‐in‐six children have a disability (Zablotsky et al, 2019), 50% of whom may experience bullying (Jackson, Vaughn, & Kremer, 2019).…”
Section: Discussionmentioning
confidence: 99%